PENGUATAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA POLITEKNIK MELALUI PENDEKATAN “CONCEPT TEACHING” PADA TOPIK FLUIDA DINAMIS - I Gede Rasagama (Jurnal Pendidikan Fisika, 2018)
There is rationality to the importance of developing students' critical thinking skills. It is possible to integrate direct presentation, concept formation, and concept attainment in a single learning approach. There is essence, functionality, and urgency of dynamic fluid concept for polytechnic students. The objective of the research is to produce a conceptual learning teaching model of dynamic fluid topic and to know its impact on strengthening students' critical thinking skill. Research subjects were 28 students, IB Class, Mechanical Engineering Study Program, DIII, Bandung State Polytechnic.. The study used quasi-experimental methods, and one group pre-test post-test design. Research instruments include lesson plans, LKM, PG questions, and questionnaires. Data analysis used statistical test, gain normalization, and descriptive analysis. The results show that the concept teaching approach on the topic of dynamic fluid has strengthened students' critical thinking skills significantly. The student's response to the overall concept teaching approach is quite good. The steps of concept teaching approach and the development of critical thinking skills are felt by the students quite easily, whereas the dynamic fluid material is considered difficult.